2011
DOI: 10.1258/ebm.2011.011008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate-to-severe chronic kidney disease on flow-mediated dilation and progenitor cells

Abstract: A reduction in progenitor cell populations that help preserve vascular continuity and induce vascularization may accentuate endothelial cell apoptosis and dysfunction, ultimately contributing to organ failure and increased cardiovascular disease in chronic kidney disease (CKD). We hypothesized that CD45+ myeloid and CD34+ hematopoietic circulating progenitor cell (CPC) subpopulations would be reduced, peripheral blood mononuclear cell (PBMNC) colony-forming units (CFU) would be impaired, and flow-mediated dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…These findings are consistent with previous studies of vascular function in the population with CKD. Several studies have reported impairments in conduit artery function in kidney failure and in patients with mild to moderate CKD, as assessed by brachial artery flow-mediated dilation, a measure of endothelium-dependent dilation (17,27,42). In patients with renal failure, several studies have observed impairments in microvascular function via venous occlusion plethysmography (2) and a local heating stimulus (70).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with previous studies of vascular function in the population with CKD. Several studies have reported impairments in conduit artery function in kidney failure and in patients with mild to moderate CKD, as assessed by brachial artery flow-mediated dilation, a measure of endothelium-dependent dilation (17,27,42). In patients with renal failure, several studies have observed impairments in microvascular function via venous occlusion plethysmography (2) and a local heating stimulus (70).…”
Section: Resultsmentioning
confidence: 99%
“…EPCs constitute the main cellular mechanism of repair of the vascular endothelium [9,29]. It has been demonstrated that the number of circulating EPCs may serve as a non-invasive method of evaluating endothelial function, and a decrease in their numbers may be considered a cardiovascular risk factor in individuals with or without manifest CVD [30]. Hill et al [31] found a negative correlation between the number of EPCs and the Framingham risk scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction, which primarily results from the impairment of the vasodilating regulatory functions of the endothelium, smooth muscle cell proliferation and fibrinolysis [3] , is emerging as a very important mediator along with nontraditional CVD risk factors in patients with CKD [4]. Thus, it is an attractive target for interventions designed to reduce the risk and burden of CVD in patients with CKD [5].…”
Section: Introductionmentioning
confidence: 99%